2013
DOI: 10.1667/rr3008.1
|View full text |Cite
|
Sign up to set email alerts
|

Low-LET Proton Irradiation of A549 Non-small Cell Lung Adenocarcinoma Cells: Dose Response and RBE Determination

Abstract: Since 1957, broad proton beam radiotherapy with a spread out Bragg peak has been used for cancer treatment. More recently, studies on the use of proton therapy in the treatment of non-small cell lung cancer (NSCLC) were performed and although the benefit of using protons for the treatment of NSCLC is recognized, more work is needed to gather additional data for the understanding of cell response. Human A549 cell survival was evaluated by colony forming assay 11 days after 10 keV/μm proton beam irradiation at 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…The existence of HRS after acute low-dose X-ray exposures is now irrefutable. More recently, cell line studies have also demonstrated HRS after high linear energy transfer (LET) exposures (Tsoulou et al 2001, Xue et al 2009, Petrovic et al 2010, Wera et al 2013, supporting earlier reports using single doses of pi-mesons or neutrons (Marples et al 1994, Marples andSkov 1996).…”
Section: Discussionsupporting
confidence: 68%
“…The existence of HRS after acute low-dose X-ray exposures is now irrefutable. More recently, cell line studies have also demonstrated HRS after high linear energy transfer (LET) exposures (Tsoulou et al 2001, Xue et al 2009, Petrovic et al 2010, Wera et al 2013, supporting earlier reports using single doses of pi-mesons or neutrons (Marples et al 1994, Marples andSkov 1996).…”
Section: Discussionsupporting
confidence: 68%
“…1 illustrates the flow chart for implementing mitotic catastrophe. This simple mechanism is in good agreement with the general consensus of how mitotic catastrophe occurs 35 and it circumvents the need to introduce another parameter required for the cell death delay model that we and others have previously used 6, 33 . It also neglects senescence and apoptosis as other mechanisms for radiation-induced tumour cell death.…”
Section: Resultssupporting
confidence: 78%
“…Death and cell clearing is not instantaneous after exposure and tumours undergoing radiotherapy do not shrink at the rate one would expect from measured in vitro cell death. Recent clonogenic survival data on lung cancer cells have in fact shown that it can take as long as 14 days post-exposure before a cell actually disappears 33 . Similarly, we have shown using time lapse imaging of normal human breast cells in vitro 34 that cell death is asynchronous following exposure to the same dose of x-rays with large variations between cells.…”
Section: Resultsmentioning
confidence: 99%
“…47 A recent experiment in a human NSCLC cell line reported an RBE 5 1.9 for 3.9 MeV protons compared with X-rays. 48 The Tsukuba proton beam line used for the NSCLC treatment 42 has been used for in vitro experiments in different human cell lines. 49 Apoptosis induction was greater than two-fold the level induced by 10 MeV X-ray.…”
Section: Hypofractionationmentioning
confidence: 99%